Botulism during SARS-CoV-2 pandemic: The importance of differential diagnoses. (August 2021) - Gatto, Antonio; Pulitanò, Silvia Maria; Conti, Giorgio; Soave, Paolo Maurizio; Di Sarno, Lorenzo; Chiaretti, Antonio
Abstract: Botulism is a neuroparalytic syndrome caused by a neurotoxin produced by Clostridium botulinum . We describe a patient with neurological symptoms associated with intoxication by Clostridium botulinum and infection by SARSCoV2. This report underlines that it is mandatory, even in case of SARS-CoV-2 positivity, to investigate all the causes of a clinical pattern. Highlights: Botulism is a neuroparalytic syndrome caused by a neurotoxin produced by the Clostridium Botulinum. Considering the SARS-CoV-2 pandemic, in patients with neurological symptoms, this infection must be considered. Considering neurological manifestations of COVID-19, some of them are associated also to a botulinum-like clinical pattern. If there's overlap of clinical signs a detailed medical history should be collected in order to make differential diagnosis.